2019
DOI: 10.1177/2382120519891178
|View full text |Cite
|
Sign up to set email alerts
|

Using a Problem/Case-Based Learning Program to Increase First and Second Year Medical Students’ Discussions of Health Care Cost Topics

Abstract: Background:The rising costs of health care in the United States are unsustainable and gaps in physician knowledge of how to provide care at a lower cost remains a contributing factor. It has been suggested that learning about health care costs should be incorporated into existing, already overburdened medical school curricula.Objective:To increase the discussion of health care costs among first and second year medical students, we added a component of health care cost education to an existing problem/case-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that there have been attempts to implement either the PBL or the CBL teaching model in the delivery of various college and university majors, [ 9 , 11 , 13 , 21 ] but few have paid attention to combined PBL–CBL teaching in clinical medicine. Ginzburg et al applied the combined PBL–CBL teaching method to medical students’ discussions about cost-related healthcare topics, showing that PBL combined with CBL is an effective method for engaging in conversations related to public health [ 35 ]. Another study implemented the combined PBL–CBL teaching method in six courses to improve students’ leadership skills without occupying curricular training time [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that there have been attempts to implement either the PBL or the CBL teaching model in the delivery of various college and university majors, [ 9 , 11 , 13 , 21 ] but few have paid attention to combined PBL–CBL teaching in clinical medicine. Ginzburg et al applied the combined PBL–CBL teaching method to medical students’ discussions about cost-related healthcare topics, showing that PBL combined with CBL is an effective method for engaging in conversations related to public health [ 35 ]. Another study implemented the combined PBL–CBL teaching method in six courses to improve students’ leadership skills without occupying curricular training time [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ginzburg et al (2019) explored the effectiveness of a hybrid instructional approach combining problem-based learning and case-based learning during students' discussions in the context of public health. The findings revealed that both methods were successful in enhancing conversations on public health issues.…”
Section: Figure 1 Descriptive Results Of Collaboration Skillsmentioning
confidence: 99%
“…Figure 1 illustrates the presence of cited references hailing from journals categorized as Business, Economics, Linguistics, Management, and Sociology. For example, the citing of business, economics and management journals may provide evidence of the increasing complexity of healthcare systems and medical education researchers’ efforts to inform education with topics like leadership [23, 24] and healthcare cost consciousness [25, 26]. Additionally, the inclusion of linguistics may be a nod towards the rise in electronic medical records and the novel language analysis methods used to mine them [27, 28].…”
Section: Discussionmentioning
confidence: 99%